2022
DOI: 10.12688/f1000research.76181.1
|View full text |Cite
|
Sign up to set email alerts
|

Parental coronavirus disease vaccine hesitancy for children in Bangladesh: a cross-sectional study

Abstract: Background: Coronavirus disease 2019 (COVID-19) requires mass immunization to control the symptoms and global spread of severe acute respiratory syndrome coronavirus 2. Data from developed countries reported a high prevalence of parental COVID-19 vaccine hesitancy. However, parental vaccine hesitancy data in countries with low and middle income are scarce. The goal of this study was to assess the prevalence of parental vaccine hesitancy and identify subgroups with higher odds of vaccine hesitancy. Methods: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…This is in line with previous research showing a positive association between parents’ compliance with pandemic-related policies and the decision to vaccinate their children against COVID-19 [ 24 , 55 ]. Moreover, previous research found that this association was present for other vaccines in addition to the COVID-19 vaccine [ 56 ]. Hence, the tendency to accept the COVID-19 vaccine for children seems to be related to the overall adherence to vaccination policies [ 57 ].…”
Section: Discussionmentioning
confidence: 90%
“…This is in line with previous research showing a positive association between parents’ compliance with pandemic-related policies and the decision to vaccinate their children against COVID-19 [ 24 , 55 ]. Moreover, previous research found that this association was present for other vaccines in addition to the COVID-19 vaccine [ 56 ]. Hence, the tendency to accept the COVID-19 vaccine for children seems to be related to the overall adherence to vaccination policies [ 57 ].…”
Section: Discussionmentioning
confidence: 90%
“…The final pool of the studies comprised a sample size ranging from 223 to 5,237 participants with an average study sample of 1,325 and a total of 23,854 participants across all eighteen studies included (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Our review included a total of one study from Afghanistan, five from Bangladesh, eight from India and four from Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…This trend was also observed in the United States of America (USA), where vaccinated adults were less likely to consent to have their children vaccinated against COVID-19 ( 10 ). A Bangladeshi study showed that parental vaccine hesitancy could be as high as 42.8% ( 11 ). Other Asian countries also demonstrated that parental hesitancy relatively lower at 10.8%–11.8%, in Taiwan and Vietnam respectively ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%